RETRACTED: Designing a system call analyser for system calls used inside Linux containers - Nuriev Marat; Zaripova Rimma; Tazieva Ramilya; Gazetdinov Shamil; Valiev Marat (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001